Using Simulation to Improve Communication Skills in Nurse Practitioner Preceptors. Issue 1 (January 2017) - Murray, Linda Aveni; Buckley, Kathleen
Abstract : Role transitions in nursing may lead to stress and anxiety or the novice, which can be decreased with appropriate mentoring by preceptors. However, preceptors commonly describe having a lack of mentoring skills. This project focused on nurse practitioner preceptors and their gap in mentoring communication skills when handling difficult communications with novice nurse practitioners. The use of a simulation as a means for learning communication skills was evaluated for its effect on increasing preceptor skill level in mentoring.